Levels of Theoretical Generalizations in the Course of Physics of the Continuing Education System (International Journal of Psychosocial Rehabilitation, 2020)
In the article, the concepts and laws that make up the knowledge system of a physical theory are called substantive or theoretical generalizations. They are represented by concepts, laws, theories, and ideas of the physical picture of the world. Studying the course of physics in lifelong education is aimed at developing students' thinking, forming their scientific picture of the world, and mastering the methods of cognition of nature.